Universitary financing and welfare: A dynamic analysis with heterogeneous agents and overlapping generations - Sánchez, Juan Matías (2003)
This paper develops a model in which it is possible to evaluate alternatives of human capital financing. The alternative systems under discussion are: total feeing; graduates taxes and uniform taxes (this can be associated to the scheme presently used in the Argentina universitary system). Assessment of the alternatives is performed over welfare, based on the indicators of poverty, equality, equity (justice in the distribution) and the average levels of utility and wealth. Likewise, the functions of welfare presented by Bentham, Rawls, Atkinson, Sen and Kakwani are also considered. The most remarkable results are obtained through the simulation of an economy under three scenarios. In that way, the system of graduates taxation is found to be better for welfare; whereas the system of uniform taxation only can be justified as it maximises the number of students. In addition, an analysis of political economy in this model helps to understand why a system of uniform taxation can be sustainable on the time.